Sistematis Literatur Review (SLR) : Peningkatan Kapasitas dan Pengelola Sumber Daya dalam Usaha Mikro, Kecil dan Menengah pada Badan Usaha Milik Desa - Hambali Hanafia; Irzami Hawa; Katarina Rika Apriliana; Iriyanti Iriyanti; Agus Munandar (Departement of Mathematics Education, 2023)
The purpose of this study is to analyze capacity building and resource management in micro, small and medium enterprises, village-owned enterprises, namely in the field of human resource development and training in several villages by providing ongoing assistance and collaborating with various parties. The study used a systematic literature review approach through several stages, namely identifying research questions, establishing a data base for research results, selecting relevant research results and indexing data extraction, synthesizing results using narrative methods and presenting data. Methodology This research was conducted with a search engine (Google Chrome) using the address https://scholar.google.com/ chosen according to the address of the largest open database website that can be accessed by many parties who search with the search term